Service Quality, Product Completeness and Price on Consumer Purchasing Decisions - Syahnadin, Muhammad Fikra; Karunia, Erick; Apriadi, Dodi; Loong, Ang Hong; Madli, Faerozh; Gulabdin, Shaierah; Haibo, Li (Advances in Business & Industrial Marketing Research, 2025)
Purpose: This study aims to examine the influence of service quality, product completeness, and price on consumer purchasing decisions at MR.DIY in Tarakan City. Research Design and Methodology: A quantitative approach was applied using a survey method. The data were collected through non-probability sampling with a purposive sampling technique. The sample consisted of 190 consumers who had made at least two purchases at MR.DIY. The variables in this study were measured using a Likert scale. Multiple linear regression analysis was employed as the primary statistical tool, processed through SPSS version 25. Findings and Discussion: The results revealed that service quality has a positive and significant influence on purchasing decisions, indicating that better service can enhance consumers’ intention to buy. Similarly, product completeness showed a significant positive effect, suggesting that a wide variety of available products increases consumer confidence in making a purchase. Price also demonstrated a considerable positive impact, confirming that affordable and competitive pricing supports consumer decision-making. Implications: This study implies that retail management, particularly at MR.DIY Tarakan should focus on improving service delivery, ensuring product availability tailored to local needs, and offering competitive pricing strategies to stimulate customer purchasing behavior and business sustainability.